The Antioxidant Effect of Colombian Berry (Vaccinium meridionale Sw.) Extracts to Prevent Lipid Oxidation during Pork Patties Shelf-Life - Márcio Vargas-Ramella; José M. Lorenzo; Sol Zamuz; María Esperanza Valdés; Daniel Moreno; María C. Guamán Balcázar; José M. Fernández-Arias; Jorge F. Reyes; Daniel Franco (MDPI AG, 2021)
A scarce amount of knowledge about the use of Colombian berry (CB) in meat products is available in the literature. This work studies the impact of the addition of CB extracts (CBE) on pork patties at three different concentrations in the range 250-750 mg/kg. CBE were characterized in terms of their polyphenolic profile and antioxidant activity [1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging capacity, half maximal inhibitory antioxidant concentration (IC50), 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), ferric reducing antioxidant power assay (FRAP) and oxygen radical absorbance capacity (ORAC) tests)]. After pork patties elaboration, instrumental and sensorial colour, as well as lipid oxidation measured as thiobarbituric acid reactive substances assay (TBARS) values, were evaluated for 10 days of refrigerated storage in a modified atmosphere (80% O2-20% CO2). The total anthocyanin composition represented 35% of the polyphenolic substances of the CBE, highlighting high contents in cyanidin derivatives. Additionally, other flavonoids (quercetin and kaempferol compounds) and phenolics acids, substances positively related to antioxidant activity, were identified and quantified. In addition, the incorporation of CBE resulted in improvements in colour and lipid stability of pork patties, especially for the highest concentration used. Our findings demonstrated that CBE could be added to pork patties without impairing their sensorial profile. Overall, our results indicate that the use of CBE as a source of natural antioxidant, natural colourant, or even as a functional ingredient could be promising, but more studies are necessary to confirm it.